Skip to main content

All Questions

4 votes
1 answer
496 views

Can we convert this statement about sets into a statement of propositional logic?

A question was just asked here about proving $$A⊆(B∪C)⟺A\setminus C⊆B.$$ We can prove this statement directly, using the concepts of first-order logic. "Suppose $x \in A \setminus C$ and that $A⊆(...
goblin GONE's user avatar
  • 68.1k
7 votes
4 answers
4k views

proving logical equivalence $(P \leftrightarrow Q) \equiv (P \wedge Q) \vee (\neg P \wedge \neg Q)$

I am currently working through Velleman's book How To Prove It and was asked to prove the following $(P \leftrightarrow Q) \equiv (P \wedge Q) \vee (\neg P \wedge \neg Q)$ This is my work thus far $...
Bryan Baraoidan's user avatar
2 votes
2 answers
5k views

How to apply De Morgan's law?

If for De Morgan's Laws $$( xy'+yz')' = (x'+y)(y'+z)$$ Then what if I add more terms to the expression ... $$(ab'+ac+a'c')' = (a'+b)(a'+c')(a+c)?$$
diegoaguilar's user avatar
7 votes
2 answers
977 views

Which law of logical equivalence says $P\Leftrightarrow Q ≡ (P\lor Q) \Rightarrow(P\land Q)$

I'm going through the exercises in the book Discrete Mathematics with Applications. I'm asked to show that two circuits are equivalent by converting them to boolean expressions and using the laws in ...
Adam's user avatar
  • 71
3 votes
1 answer
470 views

Boolean Algebra Transform

I am revisiting Boolean algebra after a long while. Can somebody help show me how to simplify the LHS to get the RHS? $$abc * a'bc + (abc)' * (a'bc)'\quad = \quad \;b'+c'$$
John Roberts's user avatar
2 votes
2 answers
397 views

How to prove that $(A \lor B) \land (\lnot A \lor B) = B$

I know this is fairly basic, and I understand that it becomes $$ \begin{align} (A \land \lnot A) \lor B \\ F \lor B \\ B \end{align} $$ However, I can't work out how to prove that it becomes that ...
Callum M's user avatar
  • 269
23 votes
3 answers
130k views

De-Morgan's theorem for 3 variables?

The most relative that I found on Google for de morgan's 3 variable was: (ABC)' = A' + B' + C'. I didn't find the answer for my question, therefore I'll ask here: ...
Billie's user avatar
  • 3,470
30 votes
5 answers
99k views

Prove XOR is commutative and associative?

Through the use of Boolean algebra, show that the XOR operator ⊕ is both commutative and associative. I know I can show using a truth table. But using boolean algebra? How do I show? I totally have no ...
Lawrence Wong's user avatar
2 votes
2 answers
6k views

Simplifying the following expression using Boolean Algebra

Simplify the following expression using Boolean Algebra into sum-of-products (SOP) expressions . refers to AND + refers to OR a'.b'.c' + a.b'.c' + a.b.c' This is what I have so far. a'.b'.c' + a....
Lawrence Wong's user avatar
0 votes
2 answers
3k views

Boolean Algebra equivalency

Which Boolean algebra laws are required to show that $$(\lnot y \land \lnot z) \lor (x \land ((\lnot y \land z) \lor (y \land \lnot z))) = (\lnot y \land \lnot z) \lor (x\land (\lnot (y \land z)...
Matt Munson's user avatar
  • 1,557
2 votes
4 answers
158 views

Proof that $B \land ( B \lor C) = B$?

In my logic design exam today I was given this question: Show that: $$ B \land ( B \lor C) = B $$ It's asking for a proof for this expression. Could someone please explain how such expression ...
user avatar
1 vote
0 answers
737 views

Inverse function in multi-valued logic through the Webb function

Let Webb function in multi-valued logic as $Webb(x, y) = W(x, y) = Inc(Max(x, y))$. There is a theorem about any function in any multi-valued logic can be represented through the Webb function. Then ...
Ivan Kochurkin's user avatar
1 vote
1 answer
592 views

Transforming statements of a query language to propositional logic

I have a custom query language which expresses containment relations between variables. Containment in this context is simply an object (A) in programming language X (java/C#/python etc: a language ...
mahonya's user avatar
  • 113
2 votes
2 answers
4k views

Boolean Simplification: (A+C)(!A+B)(B+C) = BC

How might I solve this? I can't find any problem similar to this, and I always end up with the wrong terms. If (AB) = 0 and (A+B) = 1, prove that (A+C)(!A+B)(B+C) = BC
user1764389's user avatar
-1 votes
2 answers
2k views

Boolean Algebra - Truth Table

X'Y'Z' + XYZ I have the equation above (Boolean Algebra truth table), and as I know, if I get x' and the value of x is 0, the value will change to 1. But Y' with the top bar being higher, what ...
Dragon Void's user avatar

15 30 50 per page